SOME FUNDAMENTAL ISSUES REGARDING JUDICIAL APPEALS OF PRE-JUDICIAL ACTS BY PUBLIC PARTICIPANTS IN CRIMINAL PROCEEDINGS - Dilbandyan, Samvel (State and Law, 2025)
This scientific article is dedicated to the judicial appeal of pre-trial procedural acts performed by public participants in criminal proceedings. It examines the subjects entitled to appeal, the written and oral procedures for examining appeals, as well as the evidentiary process related to facts under appeal in judicial proceedings.The Criminal Procedure Code establishes a system of guarantees designed to protect the rights and legitimate interests of individuals within the framework of criminal proceedings. Appealing the actions and decisions of public participants during pre-trial proceedings is one of the key guarantees that enables judicial review of the legality of procedural acts carried out by public participants.The new Criminal Procedure Code provides detailed regulation of the scope of judicial appeals concerning pre-trial procedural acts, the parties entitled to appeal, the powers of the court, and the participants involved in the proceedings. A review of judicial practice reveals numerous cases involving appeals against the actions and decisions of public participants in pre-trial proceedings. This underscores the significance of challenging pre-trial procedural acts and highlights the necessity of ensuring their effective application in practice.
Keywords: criminal proceedings; pre-trial proceedings; procedural act; appeal; participants; grounds for appeal; initiation of criminal proceedings; appellant